Досвiд використання водних iндексiв супутникових зйомок TERRA/MODIS для монiторингу засухи пiвденних районiв України на прикладi вегетацiйного перiоду 2007 року - Сахацький, О. I. (Видавничий дім "Академперіодика" НАН України, 2008)
The paper presents the results of using the satellite data from TERRA/MODIS for the drought monitoring within the south regions of Ukraine for the vegetation period of 2007 as an example. The water index NWI calculated on the base of spectral reflectance of Green (Ch4) and SWIR (Ch6) channels of TERRA/MODIS data has been used for the evaluation of a drought level. The proposed approach will be useful for the solution of the problems concerning the agriculture, natural resources, and nature protection.